The EA Sports League on Instagram: from visual importance to audience rankings - Ye, Haokeqian; Francisco Javier Herrero Gutiérrez (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This work examines the visibility of Spanish clubs in the EA Sports League on Instagram. Using mainly quantitative techniques the objectives pursued are related to the presence of these clubs on the aforementionedsocial network, as well as establishing a ranking, the life span of these accounts, the number of posts and content analysis in the form of photographs and reels. The results and conclusions show that Real Madrid, FC Barcelona and Atlético de Madrid lead the ranking in terms of the number of followers. There is no specific period in which this social network had a greater impact on the creation of their accounts, while the rate of posting varies. When examining the content of the top 5 clubs with the highest number of followers, it becomes evident that most of their photo posts predominantly feature images of players, whereas their reel videos frequently showcase highlights from matches